Optimasi Pengambilan Triterpenoid dari Daun Pegagan (Centella Asiatica) dengan Metode Ekstraksi Bertingkat - Dewi Wahyuningtyas; Haidir Febbyansyah Saputra; Sri Sunarsih (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2021)
Pegagan (Centella asiatica) has potential as a medicinal plant because of its triterpenoids content. It can be used to accelerate the healing of bleeding wounds on the skin. This study aims to optimize ethanol volume and extraction time on triterpenoid yields obtained and to determine the physical characteristics of the extract of pegagan leaves by using soxhlet extraction method. Three main processes were first extraction using n-hexane as solvent at a temperature of 69oC for 120 minutes, then second extraction from the residue using a varied volume of ethanol as a solvent (250; 275; 300; 325 mL) at a temperature of 78oC for varied time (60; 90; 120; 150 menit), and drying the filtrate using a rotary evaporator. The results shown that when the volume of solvent and extraction time increased, the triterpenoid yields increased too. The optimal volume of ethanol was obtained at 300 mL for 120 minutes in extraction time with the triterpenoid yields of 0.59%.